Revitalisasi Griya Pangan Sejahtera agar Perekonomian Rumah Tangga di Desa Carangwulung Berjaya - Fadhlurrahman,; Dwirana, Adinda; Rosy, Brillian (Abimanyu : Jornal of Community Engagement, 2023)
Carangwulung Village is a village located on the slopes of Mount Anjasmoro climbing, Wonosalam District, Jombang Regency. This village has 6 hamlets including the hamlets of Gondang, Banyon, Carangwulung, Segunung, Ngeseng, and Bangunrejo. Carangwulung is a tourist village where several hamlets have developed but there is no special treatment to improve the tourism branding. This location is supported by the presence of shady trees so that it gives the impression of a beautiful view. However, the community is considered less able to take advantage of the large yard land. Therefore, we propose a program called “Griya Pangan Sejahtera” which aims to beautify the yard of the house to make it look neat. In addition, this program aims to improve the economy and save household expenses. The method used in running this program is a qualitative method with observation techniques.